Las colocaciones de crédito efectuadas por las cooperativas de ahorro y crédito del segmento 1 de la ciudad de Loja periodos 2019-2021. - Basurto Leon, Bryan Stiven (2024)
The following research was developed based on the general objective of analyzing the credit placements made by the COAC'S of segment one of the city of Loja for periods 2019-2021, for which it was necessary to conduct a study of the credit portfolio of the savings and credit cooperatives of segment 1 such as Padre Julián Lorente and Vicentina Manuel Esteban Godoy Ortega, It was found that the two institutions have similar products and services, and management strategies were designed for the loan portfolio based on the foundations found, using indicators from the PERLAS monitoring system to identify protection, effective financial structure, yield rates and costs, The indicators of the PERLAS monitoring system were used to identify protection, effective financial structure, yield rates and costs, asset quality and signs of growth, finding that the savings and credit cooperatives analyzed have a placement percentage below 70% of the loan portfolio, and that the CoopMego cooperative has a delinquency rate of 7%; the institutions have problems in the growth of their loans because they do not meet the established goal, concluding that it is necessary to establish strategies for the recovery of the loan portfolio in order to obtain acceptable recovery margins that comply with the established goal and thus reduce delinquency levels, applying constant training processes for credit and collection personnel and thus, through control and efficiency in the placement and recovery of its loans, be reflected in a healthy and productive portfolio.